Antimalarial activity of selected Ethiopian medicinal plants in mice - Eshetu M. Bobasa; Biniyam G. Alemu; Shibiru T. Berkessa; Moti Y. Gemechu; Fanta G. Fufa; Gemechu Z. Cari; Wote A. Rike (GarVal Editorial Ltda., 2018)
Context: Parasites are the leading killers in subtropical areas of which malaria took the lion share from protozoan diseases. Measuring the impact of antimalarial drug resistance is difficult, and the impact may not be recognized until it is severe, especially in high transmission areas. Aims: To evaluate the in vivo antimalarial activities of hydroalcoholic extracts of the roots of Piper capense and Adhatoda schimperiana, against Plasmodium berghei in mice. Methods: Four-day suppressive and curative test animal models were used to explore the antimalarial activities of the plants. 200, 400, and 600 mg/kg of each plant extract was administered to check the activities versus vehicle administered mice. Mean survival time and level of parasitemia were the major variables employed to compare the efficacy vs. negative control. Results: In both models the 400 and 600 mg/kg doses of Adhatoda schimperiana and the 600 mg/kg dose Piper capense. showed significant parasitemia suppression and increased in mean survival time at p≤0.05. The middle dose of Piper capense had a border line inhibition where the extracts were considered active when parasitemia was reduced by ≥ 30%. Conclusions: The hydroalcoholic extracts of the roots of Adhatoda schimperiana and Piper capense possess moderate antimalarial activities, which prove its traditional claims. Thus, further studies should be done to isolate the active constituents for future use in the modern drug discovery.